PROBLEMATIKA PERKULIAHAN ANALISIS REAL: STUDI LITERATUR REVIEW: Real Analysis Lecture Problematics: Literatur Review Study - Rambe, Ahmadsyah Fauzian; Hasanah, Rusi Ulfa; Aisyah, Nur; Dari, Wulan (Yayasan Al-Amin Qalbu, 2024)
This article was prepared with the aim of analyzing the problems that occur in real analysis lectures experienced by undergraduate mathematics or mathematics education students. This research is a literature study research with the method used, namely Systematic Review (SR) or generally called Systematic Literature Review (SLR) which focuses on real analytical problems, which begins by identifying and evaluating literature that is relevant to the problem being discussed. Data analysis was carried out using an interactive model which uses 4 steps in the analysis stages, namely: 1) Data collection, 2) Data condensation, 3) Data presentation and 4) Data verification (conclusion). This research identified 5 previous articles. The problems that exist in the real analysis lectures of the five are: students still don't understand the purpose and purpose of the questions, so they can't solve the questions well and the factor that makes them not understand is because they don't understand the pre-requisite material such as sets, number systems and others. Another problem is that they cannot understand and use mathematical language, and they also do not understand mathematical notation. To overcome this problem, the lecturer must know whether the students have understood the pre-requisite material for real analysis or not, because if students do not understand it, in the future it will definitely be difficult for them to understand the material or prove theorems and so on. Apart from that, you can apply lesson study and give students an explanation first regarding the material being studied, then practice.